Management of Hatching Eggs and Broiler Performance - Gary D. Butcher; Amir H. Nilipour (EDIS, 2003)
Broiler performance in the field is dependent to a large extent on egg management practices. Quality management for each step of the broiler production chain involving formation of the egg, oviposition, egg handling, incubation, hatching, brooding, and broiler grow-out is essential and will affect profitability. The ultimate objective of any integration is producing high quality, healthy and vigorous chicks that have the potential to yield meat at the lowest cost per pound. This document is VM128, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 1, 2002.